How best to assess quality of life in informal carers of people with dementia; A systematic review of existing outcome measures. - Johanne Dow; Jonah Robinson; Shannon Robalino; Tracy Finch; Elaine McColl; Louise Robinson (PLoS ONE)
Background In the UK, there are currently 800 000 people living with dementia. This number is expected to double in the next 20 years. Two-thirds of people with dementia live in the community supported by informal carers. Caring for a person with dementia has adverse effects on psychological, physical, social wellbeing and quality of life. The measurement of quality of life of carers of people with dementia is increasingly of interest to health and social care practitioners and commissioners, policymakers, and carers themselves. However, there is lack of consensus on the most suitable instrument(s) for undertaking this. Methods A systematic review of the literature using COSMIN methodology. Searching of electronic databases (Medline, PsycINFO, CINAHL and Web of Science), reference list and citation searching of key papers was undertaken. COSMIN methodology was used to simultaneously extract data from and assess methodological quality of included studies, and make a recommendation for the instrument with the most high quality evidence for its measurement properties. Results Ten instruments were suitable for inclusion in this review. The Carer well-being and support questionnaire (CWS) has the best quality evidence for the greatest number of measurement of properties. The Caregiver Well-Being Scale is also worthy of consideration. There is not presently a measure which could be recommended for use in economic evaluations, however the Impact of Alzheimer's Disease on the Caregiver questionnaire (IADCQ) could potentially be used following further investigation of its measurement properties in a representative population. Conclusion The CWS is the most appropriate instrument to recommend for the assessment of quality of life in informal carers of people with dementia at present. All instruments included in this review would benefit from more rigorous evaluation of their measurement properties.